The uptake and implementation of the Baby Friendly Health Initiative in Australia. Issue 3 (June 2019) - Esbati, Anahita; Henderson, Amanda; Taylor, Jane; Barnes, Margaret
Abstract: Problem: Despite evidence that implementation of the Initiative has been effective in increasing breastfeeding rates and duration of breastfeeding worldwide; the uptake is low with only 70 Baby Friendly accredited maternity facilities across Australia (approximately 23% of facilities). Background: The Ten Steps to Successful Breastfeeding and International Code of Marketing of Breastmilk Substitutes shaped the foundation for the Initiative to implement practices that protect, promote and support breastfeeding. There is evidence that implementation of the Initiative is impacted by individual and organisational culture, organisational support, and education. Organisational change is also identified as playing an important role in the successful implementation of the Initiative. Despite policy and guideline support for the Initiative at national and state levels in Australia the uptake of the Initiative is low. Aim: The aim of this research was to explore health practitioners' perspectives about the uptake and implementation of the Initiative in Australia. Methods: Semi-structured, face-to-face, telephone and Skype interviews were conducted with 12 health practitioners. Thematic analysis was used to analyse data. Results: Participants identified that the uptake and implementation of the Initiative in Australia is complex. This complexity was related to six themes: (1) policy and guideline support for the Initiative, (2) leadership support to implement the Initiative, (3) improving breastfeeding and Initiative-related knowledge, (4) improving communication between stakeholders regarding the Initiative, (5) accreditation and reaccreditation processes, and (6) implementation complexity. Conclusion: Using organisational change theories as a guide to implementation of the Initiative may be useful for facilities intending to become accredited.